2019
DOI: 10.18821/0507-4088-2019-64-3-118-124
|View full text |Cite
|
Sign up to set email alerts
|

Allokin-Alpha - New Approaches in the Treatment of Chronic Virus Epstein-Barr Infections

Abstract: Introduction. Epstein-Barr virus causes recurrent infectious mononucleosis-like symptoms. Today it is shown that the poisons of insects and animals are rich sources of antimicrobial substances (peptides) and contain a wide range of active biological compounds. Antimicrobial peptides play an important role in the immune response of the innate immunity of the host in the presence of pathogenic microorganisms. Russia has developed an antiviral drug Allokin-alpha on the basis of antimicrobial peptides. The active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The treat resulted in reduction of EBV DNA and improvement in clinical complaints for 59.67% of patients. Allokin-alpha worked by improving the recognition of virus-infected cells and suppressing viral replication (Rakitianskaya et al, 2019a). Based on these clinical studies it is recommended that Allokin-alpha therapy can be for the treatment of chronic EBVI at a dose of 1 mg subcutaneously every other day with a course dose of at least 9 injections (Rakitianskaya et al, 2019a).…”
Section: Clinical Applications Of Alloferon and Their Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…The treat resulted in reduction of EBV DNA and improvement in clinical complaints for 59.67% of patients. Allokin-alpha worked by improving the recognition of virus-infected cells and suppressing viral replication (Rakitianskaya et al, 2019a). Based on these clinical studies it is recommended that Allokin-alpha therapy can be for the treatment of chronic EBVI at a dose of 1 mg subcutaneously every other day with a course dose of at least 9 injections (Rakitianskaya et al, 2019a).…”
Section: Clinical Applications Of Alloferon and Their Analoguesmentioning
confidence: 99%
“…Allokin-alpha worked by improving the recognition of virus-infected cells and suppressing viral replication (Rakitianskaya et al, 2019a). Based on these clinical studies it is recommended that Allokin-alpha therapy can be for the treatment of chronic EBVI at a dose of 1 mg subcutaneously every other day with a course dose of at least 9 injections (Rakitianskaya et al, 2019a). Moreover, allokin-alpha demonstrated its efficacy in treating chronic fatigue syndrome in the presence of chronic herpesvirus infection.…”
Section: Clinical Applications Of Alloferon and Their Analoguesmentioning
confidence: 99%
“…It has been reported that saliva sample testing is a more informative EBV DNA identification process for chronic and atypical forms of disease. [23][24][25] EBV spreads via saliva contact and penetrates through the epithelium lining the rhinopharynx. We have demonstrated that the level of infected B cells in the population varies between 5 and 3,000 for every 10 7 B-memory cells both in the peripheral blood (average value of 110/10 7 ) and in the Waldeyer's ring (average value of 175/10 7 ), i.e., the virus evenly spreads around the ring.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%